Sporty agrovarsity - Chan, Margaret (Universiti Teknologi MARA, Sarawak, 2015)
My philosophy of sports is that beyond social and health benefits, there is also a huge potential for personal development because participating in sport competitions requires not only self restraint or self-sacrificing spirit, but responsibility and decision making on how to perform to the best of our ability to defeat the opponents. It also involves time management. My late father, who retired .as the Divisional Educational Officer always included in his speech in school athletics meets the saying, “All work and no play makes Jack a dull boy” and emphasised that sports must always be an integral part of a student’s life. As an advocate of sports, he could not stop me from being very involved in sports in my school days on the condition that I produced a good report card.